HD Video Data Transaction using Bus Mastering DMA through PCI express - et. al., Santosh Kumar B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The PCI express protocol is a novel high-speed transmission bus protocol in the industry. This paper describes a bus mastering implementation of the PCI Express protocol using a Xilinx FPGA for smooth HD video transactions [1]. The suite contains DMA controller hardware IPs, test benches, Windows driver and user application for testing transactions. Measured experimental results confirm that Xilinx Bus mastering DMA produces measured transfer speeds up to 1508MB/s (write) and 930MB/s (read) using the Xilinx ML605 development board. We hope that this project will help the additional PCI associated invention. Technologies are becoming smarter and compact daily, so we hope PCI protocol and PCI interface will add a new dimension to that development. This interface will play an important role with its significant speed and reliability.